Hoax in Social Media and It’s Threats to Islamic Moderation in Indonesia - Thaib, Erwin Jusuf (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
Hoax is a human problem in this era of information. The presence of hoaxes causes information consumers to find it difficult to distinguish between true or false information, especially those that spread on social media. The main problem in this research is how hoaxes can threaten religious moderation in Indonesia. This study aims to analyze how hoax information on social media threatens the moderation of Islam in Indonesia. This research uses the library research method. The data were obtained from relevant library data sources and analyzed using a qualitative approach. The findings show that many hoaxes are conveyed along with religious and political information. Hoax on the political aspect aims to bring down political opponents or the government. In the religious aspect, hoaxes are used to attack opposing religious beliefs or schools. Hoaxes on these two aspects, especially religion, have the potential to divide people and destroy religious moderation in society. This research is expected to contribute to the study of communication, especially media and information.